Stateful-NOR based reconfigurable architecture for logic implementation. Issue 6 (June 2015) - Mane, Pravin; Talati, Nishil; Riswadkar, Ameya; Raghu, Ramesh; Ramesha, C.K.
Abstract Most commercial Field Programmable Gate Arrays (FPGAs) have limitations in terms of density, speed, configuration overhead and power consumption mostly due to the use of SRAM cells in Look-Up Tables (LUTs), configuration memory and programmable interconnects. Also, hardwired Application Specific Integrated Circuit (ASIC) blocks designed for high performance arithmetic circuits in FPGA reduce the area available for reconfiguration. In this paper, we propose a novel generalized hybrid CMOS-memristor based architecture using stateful-NOR gates as basic building blocks for implementation of logic functions. These logic functions are implemented on memristor nanocrossbar layers, while the CMOS layer is used for selection and connection of memristors. The proposed pipelined architecture combines the features of ASIC, FPGA and microprocessor based designs. It has high density due to the use of nanocrossbar layer and high throughput especially for arithmetic circuits. The proposed architecture for three input one output logic block is compared with conventional LUT based Configurable Logic Block (CLB) having the same number of inputs and outputs; which shows 1.82×area saving, 1.57×speedup and 3.63×less power consumption. The automation algorithm to implement any logic function using proposed architecture is also presented.